Benzo(a)pyrene and cardiovascular diseases: An overview of pre-clinical studies focused on the underlying molecular mechanism - Fu, Chenghao; Li, Yuemin; Xi, Hao; Niu, Zemiao; Chen, Ning; Wang, Rong; Yan, Yonghuan; Gan, Xiaoruo; Wang, Mengtian; Zhang, Wei; Zhang, Yan; Lv, Pin (Frontiers in Nutrition, 2022)
Benzo(a)pyrene (BaP) is a highly toxic and carcinogenic polycyclic aromatic hydrocarbon (PAH) whose toxicological effects in the vessel-wall cells have been recognized. Many lines of evidence suggest that tobacco smoking and foodborne BaP exposure play a pivotal role in the dysfunctions of vessel-wall cells, such as vascular endothelial cells and vascular smooth muscle cells, which contribute to the formation and worsening of cardiovascular diseases (CVDs). To clarify the underlying molecular mechanism of BaP-evoked CVDs, the present study mainly focused on both cellular and animal reports whose keywords include BaP and atherosclerosis, abdominal aortic aneurysm, hypertension, or myocardial injury. This review demonstrated the aryl hydrocarbon receptor (AhR) and its relative signal transduction pathway exert a dominant role in the oxidative stress, inflammation response, and genetic toxicity of vessel-wall cells. Furthermore, antagonists and synergists of BaP are also discussed to better understand its mechanism of action on toxic pathways.